Boxers` personality qualities versus psychosomatics rating in different competitive situations - Grekhova, I. P.; Guzich, M. E. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to find correlations of some personality qualities (success motivations, stress tolerance etc.) with psychosomatic health rates in different sport situations. Sampled for the study purposes were 30 boxers split up into two Experimental Groups (EG): EG1 (n=15) composed of qualifiers for the top-ranking seasonal competitions; and EG2 (n=15) of the boxers who failed to qualify for the latter. Both groups were tested for the stress tolerance, psychosomatic health and individual success motivations using the Holmes and Rahe Stress Tolerance and Social Readjustment Test (`stress scale`); Giessen Psychosomatic Complaint Questionnaire; and the T. Ehlers Success Motivations scale. The study tested the both EG being exposed (regardless of the competitive standings and performance) to the uncertainty-related stressors and facing a variety of somatic problems. EG1, however, showed a strong correlation of the test rates versus the EG2 tested with little if any correlations thereof.